Methodical approaches to optimizing the insurance company portfolio of services - Tkachenko К.; Paska I. (Економіка та управління АПК, 2021)
The article is devoted to the generalization of methodological approaches to the optimization of the insurance company portfolio of services and the development of an algorithm for optimizing the insurance company's services portfolio. Insurance market of Ukraine is in a state of transformation, which is associated with changes in the institutional conditions of insurance, changes in the priorities of policyholders, macroeconomic instability, the spread of the COVID-19 pandemic. Institutional changes in the insurance market of Ukraine and macroeconomic instability have led to the "cleansing" of the insurance market and the exit of insurance companies that do not ensure transparency, solvency and efficiency. In the three quarters of 2021, 41 insurance companies left the Ukrainian insurance market, ie one in five insurance companies ceased operations. The relevance of optimizing the insurance company's portfolio of services is proved, which is due to the need for insurance companies to review their own portfolios to ensure financial stability, solvency and efficiency in a competitive insurance market of Ukraine. It is proposed to consider the optimization of the insurance company's portfolio of services as a set of interconnected and consecutive stages that are consistent and logical, as well as adaptive to modern realities of the insurance market of Ukraine, aimed at achieving profitability and maximizing the value of the insurance company. The first five stages of optimizing the insurance company's portfolio should be considered the most important, as it provides for determining the methodological principles of optimizing the insurance portfolio. Substantiation of the type of insurance company's portfolio and justification of the list of criteria for optimizing the insurance company's portfolio are interrelated stages that determine the individual basic parameters of the optimized portfolio for the insurance company depending on the chosen type of portfolio. Calculations for the optimization of the insurance company's portfolio of services involve the implementation of economic and mathematical modeling of the structure of the insurance services portfolio and the definition of its targets. Following a certain period of time, the insurance company must assess the effectiveness of achieving the optimal portfolio of services of the insurance company and the impact on key performance indicators of the insurance company, including net financial result and value of the insurance company, the presence of deviations of actual and optimal indicators.